Perancangan Video Profil Kopi Taji Lereng Bromo Sebagai Media Informasi - Muhammad Fahmi; Poerbaningtyas E; Ahmad Zakiy Ramadhan (MAVIS : Jurnal Desain Komunikasi Visual, 2023)
Taji Coffee is a collated coffee processing place in Kranjan Hamlet, Taji Village, Jabung District, Malang Regency, East Java. Taji Village is known as one of the coffee producing places on the island of Java, which has a history of coffee since the Dutch East Indies colonial era. In Taji Village, apart from enjoying a cup of coffee, visitors can also enjoy the natural beauty of the Bromo desert slopes. Taji Coffee is processed directly from local farmers, has a different coffee taste, and offers the natural beauty of the slopes of Mount Bromo. However, until now the uniqueness and advantages of Taji Village, especially the superiority of Taji coffee, are not known to the wider community. This is because Taji Coffee does not yet have good information media, the information available is limited to visitor vlog videos and several interview videos. The existing media has not shown or shown what makes Taji coffee have a different coffee taste from others. So the current conditions cannot be said to be a good information medium for introducing Taji coffee. Therefore, this research designed the Taji Lereng Bromo Coffee Profile video. The purpose of making a video profile as an information medium is to convey information about Taji coffee to the wider community. This research applies qualitative methods through three methods of observation, interviews, literature study, and using 5W 1H analysis, as well as design using the Design Thinking method. The results of the research were tested using a questionnaire using Google Form with 41 respondents. The results of the questionnaire showed that the video Profile of Taji Lereng Bromo Coffee was very good, there was information that described and explained about Taji Coffee. Kopi Taji's Video Profile as a medium of information can be distributed via social media.